(untitled) (Eurasian Journal of Ecology, 2016)
The structure of natural capital is diverse and determines the extent of the competitive advantages of the national economy. However, non-reproducible part of it is being depleted which limits the ability of the market andthereby undermining the stability of the economy of their countries as the global economy. Man posing in the course of his active life noosphere, crossed a critical threshold for intervention in wildlife, inflicting irreparable damage. The task of humanity to reduce the use of limited natural resources, replacing them with naturally renewable.